2014
DOI: 10.18632/oncotarget.1856
|View full text |Cite
|
Sign up to set email alerts
|

Tumor hypoxia enhances non-small cell lung cancer metastasis by selectively promoting macrophage M2 polarization through the activation of ERK signaling

Abstract: Hypoxia is a common phenomenon occurring in the majority of human tumors and has been proved to play an important role in tumor progression. However, it remains unclear that whether the action of hypoxia on macrophages is a main driving force of hypoxia-mediated aggressive tumor behaviors. In the present study, we observe that high density of M2 macrophages is associated with metastasis in adenocarcinoma Non-Small Cell Lung Cancer (NSCLC) patients. By applying the in vivo hypoxia model, the results suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 52 publications
4
92
2
Order By: Relevance
“…Accumulating evidence in solid tumors has shown that HIF-1α overexpression, either as a result of intratumoral hypoxia or genetic alterations, activates gene transcription, and the protein products contribute to basement membrane migration and invasion (25,37,38). In this study, treatment with sulforaphane inhibited hypoxia-induced migration by HCT116 cells (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Accumulating evidence in solid tumors has shown that HIF-1α overexpression, either as a result of intratumoral hypoxia or genetic alterations, activates gene transcription, and the protein products contribute to basement membrane migration and invasion (25,37,38). In this study, treatment with sulforaphane inhibited hypoxia-induced migration by HCT116 cells (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Numerous studies documented that the hypoxia microenvironment was able to enhance tumor progression [9,15]. A growing body of evidence demonstrated that there is a high correlation between hypoxia and lung cancer metastasis and poor prognosis [16,17]. Unfortunately, the OLV anesthesia technique, widely used during lung cancer surgery, aggravates hypoxia, which promotes the invasiveness of lung cancer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated macrophages from cycling hypoxia-exposed tumors increased cancer cell proliferation and migration in vitro [91]. In another in vivo model where mice were exposed to 8 % O 2 4 hours per day during 5 weeks, Zhang et al observed an aggressive tumor behavior with enhanced metastases that was correlated with more M2-like macrophages within the tumors [92]. Of note, Kalliomaki et al have reported that cycling hypoxia exposure induced an accumulation of tumor-associated macrophages detected by an immunostaining for F4/80, a macrophage marker, in vivo in mammary tumors of MMTV-PyMT transgenic mice.…”
Section: Cycling Hypoxia Amplifies a Tumor-promoting Inflammationmentioning
confidence: 99%